Issues Concerning Ageing Population in Kampot and Takeo Provinces, Cambodia, and the Implications of the Cambodia National Ageing Policy 2017-2030 - Soksamphoas Im (Research on Ageing and Social Policy, 2023)
This article assesses the issues concerning the ageing population in Takeo province and Kampot province, Cambodia, and the implications of the Cambodia National Ageing Policy (NAP) 2017-2030 in addressing those issues. By interviewing fifty randomly selected participants aged 60 and older, the findings revealed that the NAP 2017-2030 has not positively impacted the elderly population in Cambodia as it promised. The current generation of elderly Cambodians are Khmer Rouge conflict survivors and are financially insecure and rely on their adult children for financial support and caretaking. By closely examining the NAP 2017-2030 action plan, this study found many implications that led to slow progress and ineffectiveness. The paper concludes with a discussion on the significant issues concerning the ageing population in Cambodia today and the need for the Cambodian government to commit to implementing this ageing policy effectively.